Implementation of Tasamuh Concept in a Sociological Perspective in Multicultural Society - Imam Muhayat; Nazar Naamy (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2023)
Religion, from the beginning by sociologists, is believed to have links with other social institutions. Sociology studies religion not only in its social dimension but also in its dimension. Tasamuh contains elements of respect, appreciation and sympathy in the life of a heterogeneous or plural society, especially in religious life. The concept and reality of tasamuh practice are different. This study aims to examine the idea of tasamuh from the perspective of the sociology of religion in a multicultural society in Bali and Indonesia in general. This research uses a website study approach in a qualitative approach, in a case study design. Data collection techniques are used by conducting website research, participant observation, and documentation. Data analysis used data presentation, reduction, and conclusion, including single-site, followed by cross-site data analysis. Checking the validity of the data is done with credibility. From the explanation above, there is wisdom from tasamuh behaviour found in a multicultural society in Bali, namely a sense of calm in oneself and others, making it easier to solve problems that seem difficult for others, getting more friends, easy to get relationships, if you get difficulties you will many people help. The results of this study provide an overview of the implications of applying the tasamuh concept for multicultural societies. This is a lesson for everyone that life is not about oneself but the benefit of others.